Protein Balance and Growth Of Heifer Provided Content Rations with Different Energy and Protein - H. I., Nasrullah; Mahardika, I G.; Suryani, N. N. (Jurnal Peternakan Tropika, 2018)
This study aimed to determine the effect of protein or energy rations on protein consumption and weight gain of dara.  The research was conducted at Animal Farm of  Belok Sidan Village, Petang Sub-district, Badung Regency for three months by using 12 heifer cows were divided into three groups with initial weight/different groups as repetition.  The treatments consisted of rations containing 12% protein and 2000 kcal energy ME/kg (A), 13% protein and 2100 kcal energy ME/kg (B), 14% protein and 2200 kcal ME/kg (C) energy, and protein 15% and energy 2300 kcal ME/kg (D).  The variables observed in this study include protein consumption, weight gain, and digestible protein.  The results showed that the highest protein consumption was obtained by treatment (D) 686,56 g/h/d with statistically significant difference (P< 0.05) higher than treatment (A). The highest digestible protein was obtained treatment (D) 525,71 g/h/d statistically significantly different (P <0.05)  higher than treatment (A).  The highest stool protein obtained by treatment (A) 223,35 g/h/d was statistically significant different (P> 0.05)  higher than treatment (D).  The highest weight gain obtained by treatment (D) 422,03 g/h/d was significantly different (P <0.05) higher than treatment (A).  Based on the results of this study the rations given with protein content of 12-15% and energy 2000-2300 kkal ME/kg can affect consumption of protein, digestible protein, fecal protein, and weight gain of heifer cows. Keywords : protein and energy, weight gain, heifer cows